Problematika Penentuan Hari Raya di Indonesia Perspektif Fiqh Madhhab Penguasa - Moh. Dliya'ul Chaq (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2016)
Determination holiday in Indonesia always interesting to follow because always ended on absence of power force by government in bringing together the determination method holiday, punctuality holiday as well as the implementation of the holiday. Though fiqh legitimizes power forcefully of the government for not invite sinners, in the corridors mas?lah?ah and related issues for the people. Fiqh escorted through governments or that emerges from government in level of history more effectively and show government authority as fiqh dug by khulafâ’ al-râshidûn. Then it becomes interesting if the determination holidays in Indonesia viewed from perspective fiqh sect government. Through the model of content analysis interactif and with the document literature found two conclusions that perspective fiqh sect government (1) The Indonesian government has full authority to set the time and method of determining holiday with a model of collective diligence, in the sense chose a method of determining holiday and time holiday with representatives of community organizations. And (2) government decree through collective diligence on holiday must be obeyed and have binding force against Muslims in Indonesia.